Pengembangan Program Studi Keahlian pada SMK Sesuai Kegiatan Ekonomi Utama di Enam Koridor Ekonomi - Siswantari -- (Jurnal Pendidikan dan Kebudayaan, 2015)
The purpose of this study was to analyze the expertise study programs that need to be held in vocational secondary school and to find the development pattern of expertise competency in provincial level and/or expertise study program and expertise competency in the district/city level appropriate with its main economic activities. The study used survey and discussion method. The study used primary and secondary data. Primary data was the expertise study program needed to develop 20 main economic activities, collected by discussion with association in Main Economic Activities. Secondary data was the expertise study program conducted in 13 sample provinces, collected using questionnaires with respondent of the head of secondary education division in provincial education offices. The study showed that all provinces needed to open study programs to develop 20 main economic activities. This study concluded that expertise study program conducted in the provinces were not appropriate with its Main Economic Activities. Analysis in this study can be applied to consider opening expertise competency in the provincial level and/or expertise study program and expertise competency in district/city level.